Life cycle assessment of construction and demolition waste upcycling: A critical review of studies from 2010 to 2025 - Chen, Ying; Ou, Yifu; Mohamed, M. Shadi; Bao, Zhikang (Developments in the built environment, 2025)
Upcycling construction and demolition waste (CDW) not only enhances material performance and functional value, but also offers environmental co-benefits, thereby promoting a circular economy within the construction industry. Life Cycle Assessment (LCA) has gained widespread recognition as an effective tool for evaluating the environmental impacts of CDW upcycling. Although the body of research in this area has expanded in recent years, a systematic understanding of how LCA is applied across different upcycling practices remains limited. To address this gap, this paper aims to examine how LCA has been used to evaluate the environmental impacts of CDW upcycling. A systematic literature review was conducted, covering 46 studies published between 2010 and 2025, identified through searches in Scopus and the Web of Science Core Collection. The review reveals that recycled concrete waste materials are the primary focus of upcycling research. Among the three main upcycling methods, physical processing is the most commonly used due to its fundamental role in material transformation. A significant proportion of upcycled CDW materials is applied in structural applications, particularly as load-bearing components in buildings and infrastructure. Since upcycling technologies are still in the developmental stage, existing studies mainly focus on the environmental benefits from resource extraction to production, with particular emphasis on the impacts of CDW upcycling on air pollution and climate change. Accordingly, this study develops a Structural Framework for Upcycling and a Technical Framework for LCA, aiming to systematically integrate LCA research for CDW upcycling. Future research should concentrate on three key areas: (1) establishing a comprehensive LCA framework, (2) optimizing the sustainability of upcycling processes, and (3) improving the accuracy of LCA calculations. This study provides a valuable roadmap for researchers and practitioners to enhance LCA applications in CDW upcycling, thereby accelerating the transition toward a circular economy in the construction sector. •A systematic review of LCA applications for CDW upcycling is performed.•Physical processing is the most commonly used method for upcycling CDW.•Upcycled materials are mainly used for structural and non-structural applications.•Environmental benefits of CDW upcycling remain underexplored in LCA studies.•Energy-intensive upcycling processes challenge the sustainability of CDW reuse.